OH- IN SYNTHETIC AND NATURAL COESITE - Koch-Müller M.; Dera P.; Fei Y.; Reno B.; Sobolev N.; Hauri E.; Wysoczanski R. (My University, 2003)
The incorporation of hydrogen into the coesite structure was investigated at pressures ranging from 4.0–9.0 GPa and temperatures from 750–1300 °C using Al and B doped SiO2 starting materials. The spectra show four sharp bands (ν1, ν2a, ν2b, and ν3) in the energy range of 3450–3580 cm−1, consistent with the hydrogarnet substitution [Si4+(T2) + 4O2− = vaT2 + 4OH−], two weak sharp bands at 3537 and 3500 cm−1 (ν6a and ν6b) attributed to B-based point defects, and two weaker and broad bands at 3300 and 3210 cm−1 (ν4 and ν5) attributed to substitution of Si4+ by Al3+ + H. More than 80% of the dissolved water is incorporated via the hydrogarnet substitution mechanism. The hydrogen solubility in coesite increases with pressure and temperature. At 7.5 GPa and 1100 °C, 1335 H/106 Si is incorporated into the coesite structure. At 8.5 GPa and 1200 °C, the incorporation mechanism changes: in the IR spectra four new sharp bands appear in the energy range of 3380–3460 cm−1 (ν7–ν10) and the ν1–ν3 bands disappear. Single crystal X-ray diffraction, Raman spectroscopy, polarized single-crystal and in situ high-pressure FTIR spectroscopy confirm that the new bands are due to OH− in coesite. The polarization and high-pressure behavior of the ν7-ν10 OH bands is quite different from that of the ν1–ν3 bands, indicating that the H incorporation in coesite changes dramatically at these P and T conditions. Quantitative determination of hydrogen solubility in synthetic coesite as a function of pressure, temperature, and chemical impurity allow us to interpret observations in natural coesite. Hydrogen has not previously been detected in natural coesite samples from ultra high-pressure metamorphic rocks. In this study, we report the first FTIR spectrum of a natural OH-bearing coesite. The dominant substitution mechanism in this sample is the hydrogarnet substitution and the calculated hydrogen content is about 900 ζ ± 300 H/106 Si. The coesite occurs as an inclusion in diamond together with an OH-bearing omphacite. The shift of the OH-bands of coesite and omphacite to lower energies indicates that the minerals are still under confining pressure.
Keywords: Coesite